Socio-economic study of insecticide use on vegetable cultivation at farm level in Chittagong region (Journal of the Bangladesh Agricultural University, 2010)
The study was conducted in Satkania, Patiya and Hathazari upazilas of Chittagong district during 2008 to identify different pest problems and practices, input use and economic returns at farmers' levels. About 95% of the farmers relied on the application of insecticides to control insect pests and they said that the insecticides use was profitable. Majority of the farmers of Patiya sprayed insecticides more than 40 times in brinjal cultivation. For other selected vegetables, farmer's sprayed insecticide more than 15 times in a season. Especially for Satkania, majority of the farmers sprayed every alternative day while in the winter, the spraying frequency was reduced once a week. Pesticide dealers were the major source of information to farmers on the selection of chemicals and application methods. Very few farmers used protective measures or safety measures during pesticide application, only 39% of the respondents did not use any safety measures where 21% of the vegetable growers covered their body and faces. Eight percent covered their face and 32% covered their body at the time of spraying. On an average 61% believed that pesticide application are harmful to farm labour, 40% farmers expressed their views that pesticide application pollute water and air. Keywords: Insecticide use; Vegetable cultivation; Socio-economic characteristics DOI: 10.3329/jbau.v7i2.4745 J. Bangladesh Agril. Univ. 7(2): 343-350, 2009